A pragmatic approach to the analysis of a combination formulation - Mubtasim, Noshin; Kabir, Eva Rahman; Podder, Ashis Kumar; Bhadra, Subrata (© 2016 Elsevier B.V., 2016)
This article was published in the Saudi Pharmaceutical Journal [© 2016 Elsevier B.V.] and the definite version is available at: http://www.sciencedirect.com/science/article/pii/S1319016415001152